Teaching Impact on Telestroke Nurse Recognition of Large Vessel Occlusion Computerized Tomography Perfusion Patterns. Issue 6 (June 2020) - Williams, Laura; Helms, Maria; Snider, Emily K.; Chang, Brenda; Singh, Sam; Asimos, Andrew W.
Abstract : Background and Purpose—: A distinguishing feature of our Stroke Network is telestroke nurses who remotely facilitate evaluations. To enable expeditious transfer of large vessel occlusion (LVO) acute ischemic stroke patients presenting to nonthrombectomy centers, the telestroke nurses must immediately identify color thresholded computerized tomography perfusion (CTP) patterns consistent with internal carotid artery (ICA), middle cerebral artery (MCA) segment 1(M1), and MCA segment 2 (M2) LVO acute ischemic stroke. Methods—: We developed a 6-month series of tutorials and tests for 16 telestroke nurses, focusing on CTP pattern recognition consistent with ICA, M1, or M2 LVO acute ischemic stroke. We simultaneously conducted a prospective cohort study to evaluate the impact of this intervention. Results—: Telestroke nurses demonstrated good accuracy in detecting ICA, M1, or M2 LVO during the first 3 months of teaching (83%–94% accurate). This significantly improved during the last 3 months (99%–100%), during which the likelihood of correctly identifying the presence of any one of these LVOs exceeded that of the first 3 months ( P <0.001). There was a higher probability of correctly identifying any CTP pattern as consistent with either an ICA, M1, or M2 occlusion versus other types of occlusions or nonocclusions (odds ratio, 5.22 [95% CI, 3.2–8.5]). Over time, confidence for recognizing CTP patterns consistent with an ICA, M1, or M2 LVO did not differ significantly. Conclusions—: A series of tutorials and tests significantly increased the likelihood of telestroke nurses correctly identifying CTP patterns consistent with ICA, M1, or M2 LVOs, with the benefit of these tutorials and test reviews peaking and plateauing at 4 months. Abstract : Supplemental Digital Content is available in the text.